Fecal Microbiome Characteristics and the Resistome Associated With Acquisition of Multidrug-Resistant Organisms Among Elderly Subjects - Araos, Rafael; Battaglia, Thomas; Ugalde, Juan A.; Rojas-Herrera, Marcelo; Blaser, Martin J.; D’Agata, Erika M. C. (Frontiers in Microbiology, 2019)
Abstract Infections caused by multidrug-resistant organisms (MDRO) lead to considerable morbidity and mortality. The elderly population residing in nursing homes are a major reservoir of MDRO. Our objective was to characterize the fecal microbiome of 82 elderly subjects from 23 nursing homes and compare their resistome to that of healthy young persons. Comparisons of microbiome composition and the resistome between subjects who acquired MDRO or not were analyzed to characterize specific microbiome disruption indices associated with MDRO acquisition. An approach based on both 16S rRNA amplicon and whole metagenome shotgun sequencing data was used. The microbiome of the study cohort was substantially perturbed, with Bacteroides, Firmicutes, and Proteobacteria predominating. Compared to healthy persons, the cohort of elderly persons had an increased number, abundance, and diversity of antimicrobial resistance genes. High proportions of study subjects harbored genes for multidrug-efflux pumps (96%) and linezolid resistance (52%). Among the 302 antimicrobial resistance gene families identified in any subject, 60% were exclusively detected within the study cohort, including Class D beta-lactamase genes. Subjects who acquired MDRO or not had significant differences in bacterial taxa; Odoribacter laneus, and Akkermansia muciniphila were significantly greater among subjects who did not acquire MDRO whereas Blautia hydrogenotrophica predominated among subjects who acquired MDRO. These findings suggest that specific microbiome disruption indices may identify persons at high risk of acquiring MDRO.